Search for gluinos and scalar quarks in p(p)over-bar collisions at root s=1.8 TeV using the missing energy plus multijets signature - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2002)
A search for gluinos and scalar quarks in a data sample of 84 pb -1 of pp̄ collisions at √s = 1.8 TeV was performed. The final state of large missing transverse energy and three or more jets was investigated. The data was compared with predictions of constrained supersymmetric models and gluinos masses below 195 GeV/c 2, independent of the squark mass were excluded.